Variables explicativas del comportamiento del inversor de multifondos. Un análisis desde la perspectiva de los inversores en el sistema de pensiones chileno (2015)
This study aims to determine the variables that influence the behavior of multifund investors by analyzing whether this behavior is related to rational variables or behavioral principles. Based on data obtained from the Social Protection Survey 2006-2009 with the purpose of characterizing the investors and identifying the variables associated with their level of investment. For the data analysis data, a multiple logistic model was built in order to determine the influence of variables. The results of this research suggest that variables such as sex, age and education have an influence on the decision making of investors.